جمع القرآن الكريم ومراحله التي مر بها - القحطاني، حسين بن مسفر بن حسين (جامعة الأزهر - كلية القرآن الكريم للقراءات وعلومها بطنطا, 2022)
جمع القرآن الكريم ومراحله التي مر بها، وسأتعرض فيه لمصنفات السلف والتي تحدثت عن مراحل جمع القرآن الكريم، ليتم إلقاء الضوء على الإشكاليات الموجودة به من قبل طلاب العلم، سائلا الله عز وجل أن يوفقنا للصواب في ذلك البحث، وأن يجنبنا مواطن الذلل إنه ولي ذلك والقادر عليه. تتكون خطة هذا البحث من مقدمة، وتمهيد، وأربعة مباحث، وخاتمة، وفهرس. المقدمة: وتشتمل على: أهمية الموضوع، وأسباب اختياره، وأهداف البحث، والدراسات السابقة، ومنهج البحث، وهيكل البحث. التمهيد وفيه التعريف بمفردات عنوان البحث. المبحث الأول: كتابة القرآن وجمعه في عهد النبوة. المبحث الثاني: جمع القرآن في عهد أبي بكر الصديق. المبحث الثالث: جمع القرآن في عهد عثمان. المبحث الرابع: سمات كل مرحلة من مراحل جمع القرآن والفرق بينها، وفيه ثلاثة مطالب: الخاتمة: وفيها أهم النتائج، وأبرز التوصيات التي أخلص إليها في هذا البحث. الفهارس: وتشمل: فهرس المصادر والمراجع، والموضوعات. The collection of the Holy Qur’an and its stages that it went through), and I will present in it the works of the predecessors, which talked about the stages of collecting the Noble Qur’an, so that light is shed on the problems that exist in it by students of knowledge, asking God Almighty to guide us to the right path in that research, and to spare us the citizen of humiliation that he is the guardian It is capable of it. The plan of this research consists of an introduction, a preface, four topics, a conclusion, and an index. Introduction: It includes: the importance of the topic, the reasons for its selection, research objectives, previous studies, research methodology, and research structure. The preamble includes the definition of the terms of the research title. The first topic: the writing and compilation of the Qur’an during the era of the Prophet hood. The second topic: the collection of the Qur’an during the era of Abu Bakr Al-Siddiq. The third topic: The collection of the Qur’an during the era of Othman. The fourth topic: the characteristics of each stage of the collection of the Qur’an and the difference between them, and it has three demands: Conclusion: It includes the most important results and the most important recommendations that I reached in this research. Indexes: It includes: an index of sources, references, and topics.
Keywords: التاريخ الإسلامي -- جمع القرآن -- علوم القرآن